Tinea corporis caused by microsporum canis in children with HIV - Mariyani, Sri; Siswati, Agnes Sri; Etnawati, Kristiana (Pakistan Association of Dermatologists, 2022)
Introduction: Tinea corporis is a glabrous skin fungal infection mainly affecting children and immunosuppressed patients. The clinical feature of tinea in HIV patients shows mild inflammation that resembles other dermatoses. This report aims to establish the diagnosis and therapy choices promptly. Case: A 15-year-old boy with HIV and pulmonary TB came with complaints of itchy small red papules, exacerbated by sweating. These lesions extend almost all over the body. Dermatological examination of the chest, abdomen, back, arms and hands, and both legs showed multiple erythematous papules with annular configuration and the elevated border with scales over the erythematous base. KOH examination revealed the culture's long septate hyphae and colonies of the fungus Microsporum canis. Tinea corporis was diagnosed, and the patient was treated with oral griseofulvin and topical ketoconazole. Discussion: Microsporum canis is the third most common causative organism and is associated with 14% of cases of tinea corporis. These annular lesions resemble centrifugal erythema annular and generalized annular granulomas. A fungal culture examination was performed to confirm the diagnosis, and the tinea species were identified. Terbinafine, itraconazole, fluconazole and griseovulfin are the treatment options for tinea corporis with HIV. Conclusion: Definitive diagnosis and exact identification of the causative organism of tinea corporis could be determined by culture. Griseofulvin is still used to treat tinea, especially in liver function problems.